Structural Reform and Growth : What Really Matters? Evidence from the Caribbean - Greenidge, Kevin (IMF Working Papers; Working Paper, 2016)
Since the 1980's with the introduction of IMF/WB adjustment programs structural reforms have been a core part of the reform agenda in the Caribbean. The paper reviewed the package of structural reforms in trade liberalization, financial liberalization and tax policy, and gauges their impact on growth. The paper used a set of reform indices to gauge both short-run and long-run effects of structural reforms on growth, controlling for other possible growth determinants using panel dynamic OLS estimation. In addition, recognizing the importance of institutions to growth the empirical analysis also analyzed the impact of institutional quality on growth for a sample of small states including the Caribbean. We concluded that the benefits of structural reforms are only seen over the long-term and in reinvigorating growth the reform effort needs to be revived and include greater attention to strengthening institutional quality.